(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
In recent years, countries around the world, when developing short- and long-term budget and tax policy strategies, have been paying special attention to the introduction of various mechanisms to prevent and reduce tax evasion by taxpayers. At the same time, areas have been studied, foreign experience has been studied, and scientific and practical conclusions and proposals have been formulated on its application in our country.